Cytotoxicity analysis of Ti-7.5Mo alloy after biomimetic surface treatment to use as dental materials - Do Amaral Escada, Ana Lúcia [UNESP]; Camargo, Samira Esteves Afonso [UNESP]; De Vasconcellos, Luana Marotta Reis [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; Claro, Ana Paula Rosifini Alves [UNESP] (FapUNIFESP (SciELO), 2017)
Titanium (Ti) and its alloys are widely used for medical and dental fields due to their excellent biocompatibility, high corrosion resistance, high specific strength and excellent mechanical properties. Different methods have been developed to improve the surface properties of titanium-based implant materials, and consequently the bone-bonding ability. The Ti-7.5Mo alloy was activated by an alkaline treatment with 5M NaOH, heat treatment and subsequent immersion in SBFx5 to investigate the in vitro response of osteoblastic-like cells (MG-63) on altered biomimetic surfaces. Sample surfaces were characterized by scanning electron microscopy. Cytotoxicity was assessed by the MTT assay, total protein content, alkaline phosphatase activity (ALP) and mineralized bone-like nodule formation. It was shown the que alkali treatment led to the formation of sodium titanate and immersion in SBFx5 formed a film of calcium phosphate. The alkaline treatment and heat treatment of 7.5 Ti-Mo alloys followed by soaking them in SBFx5 for 24 hours is a suitable technique once the final samples were biocompatible, allowed the attachment of the osteoblastic-like cells (MG-G3), and increased the mineralized like-bone nodules formation by these cells.
Keywords: Biomimetic treatment; Cytotoxicity; Titanium alloys